Metallomic Approach to Mercury and Selenium in the Liver Tissue of Psectrogaster amazonica and Raphiodon vulpinus from the Brazilian Amazon - Bataglioli, Izabela [UNESP]; Vieira, José [UNESP]; Siva, Joyce da [UNESP]; Andrade, Luane [UNESP]; Faria, Victor [UNESP]; Corcoba, Rebeca [UNESP]; Almeida, Ronaldo de; Zara, Luiz; Buzalaf, Marília; Adamec, Jiri; Padilha, Pedro [UNESP] (MDPI, 2024)
This paper reports the results of a mercury (Hg) and selenium (Se) metallomic study in the liver tissues of Psectrogaster amazonica and Raphiodon vulpinus from the Brazilian Amazon. Two-dimensional electrophoresis, graphite furnace atomic absorption spectrometry, and liquid chromatography-tandem mass spectrometry were performed. Hg and Se determinations allowed the calculation of Hg:Se and Se:Hg molar ratio and Se values for health benefits (Se HBVs). The Se:Hg values were >1 for both fish species, whereas the Se HBVs were >5 for P. amazonica and >10 for R. vulpinus, indicating that both possess Se reserves to control Hg toxicity. The metallomic data allowed the identification of 11 Hg/Se-associated protein spots in the two fish species, with concentrations in the range of 9.70 ± 0.14 and 28.44 ± 0.31 mg kg−1 of Hg and 16.15 ± 0.21 and 43.12 ± 0.51 mg kg−1 of Se. Five metal binding proteins (MBP) in the Hg/Se-associated protein spots in the liver proteome of P. amazonica and eight in R. vulpinus were identified, indicating the possible formation of Hg/Se complexes on the MBP structures. The activities analysis of catalase, superoxide dismutase, GPx enzymes, and lipoperoxide concentrations demonstrated that Hg-induced oxidative stress did not occur, possibly because both fish species possess Se reserves necessary to inhibit the Hg’s deleterious effects.
Keywords: Hg and Se in Amazon fish; Hg-induced oxidative stress; metal binding proteins; metalloproteomics; Se/Hg-associated protein